Role of noninvasive ventilation in perioperative patients with neuromuscular disease: a clinical case - Marinho,Ana (2016)
The inclusion body myositis is an inflammatory myopathy that leads to chronic muscle inflammation associated with muscle weakness. It is characterized by a restrictive ventilatory syndrome requiring ventilatory support under non-invasive ventilation. The authors describe a clinical case and the anaesthetic management of a patient with inclusion body myopathy candidate for vertebroplasty, which highlights the importance of locoregional anaesthesia and of noninvasive ventilation and includes assisted cough techniques, maintained throughout the perioperative period.